The Effectiveness of e-Government at the Population and Civil Registration Office of Gowa Regency - Hardi Setiawan; Muhammad Akmal Ibrahim; Muhammad Yunus (IHSA Institute, 2023)
Electronic government has been defined as the use of information and communication technologies in government settings. This article investigates the effectiveness of e-government initiatives at the Population and Civil Registration Office of Gowa Regency across five key indicators of effectiveness: program understanding, target accuracy, timeliness, goal achievement, and real change. The research findings demonstrate that while there is a strong understanding of the program among personnel, the community faces challenges in comprehending the online-based population services. Target accuracy is achieved through the implementation of Standard Operating Procedures (SOP), ensuring adherence to predetermined rules. The program's timeliness dimension is met by providing one-day service within specified working hours. Goal achievement is observed through increased community satisfaction due to improved convenience and reduced bureaucracy. Real change is evident in enhanced transparency, accountability, and efficiency of government services. However, challenges remain, including the need to improve community understanding, expand online services, and address under-registration. By addressing these challenges and sustaining efforts for innovation, e-government can further enhance service effectiveness at the Population and Civil Registration Office of the Gowa Regency